Impact of air quality guidelines on COPD sufferers - Liu Y; Yan S; Poh K; Liu S; Iyioriobhe E; Sterling DA (International Journal of COPD, 2016)
Youcheng Liu,1,* Shuang Yan,2,* Karen Poh,1 Suyang Liu,3 Emanehi Iyioriobhe,1 David A Sterling1 1Department of Environmental and Occupational Health Sciences, School of Public Health, University of North Texas Health Science Center, Fort Worth, TX, USA; 2Department of Endocrinology and Metabolism, Fourth Affiliated Hospital, Harbin Medical University, Harbin, Heilongjiang Province, People’s Republic of China; 3Epidemiology, Human Genetics & Environmental Sciences, School of Public Health, The University of Texas Health Science Center at Houston, Houston, TX, USA *These authors contributed equally to this work Background: COPD is one of the leading causes of morbidity and mortality in both high- and low-income countries and a major public health burden worldwide. While cigarette smoking remains the main cause of COPD, outdoor and indoor air pollution are important risk factors to its etiology. Although studies over the last 30 years helped reduce the values, it is not very clear if the current air quality guidelines are adequately protective for COPD sufferers. Objective: This systematic review was to summarize the up-to-date literature on the impact of air pollution on the COPD sufferers. Methods: PubMed and Google Scholar were utilized to search for articles related to our study’s focus. Search terms included “COPD exacerbation”, “air pollution”, “air quality guidelines”, “air quality standards”, “COPD morbidity and mortality”, “chronic bronchitis”, and “air pollution control” separately and in combination. We focused on articles from 1990 to 2015. We also used articles prior to 1990 if they contained relevant information. We focused on articles written in English or with an English abstract. We also used the articles in the reference lists of the identified articles. Results: Both short-term and long-term exposures to outdoor air pollution around the world are associated with the mortality and morbidity of COPD sufferers even at levels below the current air quality guidelines. Biomass cooking in low-income countries was clearly associated with COPD morbidity in adult nonsmoking females. Conclusion: There is a need to continue to improve the air quality guidelines. A range of intervention measures could be selected at different levels based on countries’ socioeconomic conditions to reduce the air pollution exposure and COPD burden. Keywords: air pollution, biomass, chronic bronchitis, COPD, intervention